2018
DOI: 10.31101/jkk.550
|View full text |Cite
|
Sign up to set email alerts
|

Faktor risiko mempengaruhi kejadian Diabetes mellitus tipe dua

Abstract: Pasien Diabetes Mellitus dapat hidup normal dengan mengendalikan faktor risiko. Tujuan penelitian ini untuk mengetahui faktor risiko Diabetes Mellitus tipe dua. Desain studi non-eksperimental, atau juga bisa disebut dengan observasional, menggunakan desain penelitian cross-sectional. Populasi adalah warga yang berada di wilayah kerja Puskesmas I Wangon. Teknik purposif sampel sebanyak 106 orang dengan pembagian 53 kasus dan 53 kontrol. Analisa data menggunakan uji chi-square. Faktor risiko yang terbukti berpen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0
55

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(138 citation statements)
references
References 4 publications
(4 reference statements)
5
36
0
55
Order By: Relevance
“…Based on the results of the study, gender, education level, and occupation were not related to blood sugar in the Muna community. This was in line with several other studies which also showed no relationship between sex, education level, or occupation with blood sugar or the incidence of diabetes mellitus (Isnaini & Ratnasari, 2018;Krishnan, Cozier, Rosenberg, & Palmer, 2010;Rahayu, Utomo, & Setiawan, 2012).…”
Section: Blood Sugar Content Based On Muna Tribe Community's Charactesupporting
confidence: 92%
“…Based on the results of the study, gender, education level, and occupation were not related to blood sugar in the Muna community. This was in line with several other studies which also showed no relationship between sex, education level, or occupation with blood sugar or the incidence of diabetes mellitus (Isnaini & Ratnasari, 2018;Krishnan, Cozier, Rosenberg, & Palmer, 2010;Rahayu, Utomo, & Setiawan, 2012).…”
Section: Blood Sugar Content Based On Muna Tribe Community's Charactesupporting
confidence: 92%
“…This results in the body experiencing both absolute and relative insulin insufficiency. This is in line with the results of Isnaini & Ratnasari's research (2017) that most patients with DM are in the age group above 45 years of age totaling 76 (72%) respondents [15]. In this study most of the respondents at an average age of 62.89 years were not only due to organ damage related to increasing age, but also because respondents were taken during the implementation of Prolanis followed by the age group of pralansia and the elderly.…”
Section: Relationship Between Spiritual Comfort and Emotion Regulatiosupporting
confidence: 91%
“…The results showed that most patients with diabetes mellitus with complications (hyperglycemia, ketoacidosis, and gangrene) who were hospitalized, had no family history of diabetes before. This result is in line with the research cunducted by Isnaini & Ratnasari (2018) where the majority of research respondents did not have a family history of diabetes mellitus by 52.80% or 28 respondents. These results are also in line with the research conducted by Noh et al (2018) which stated that most diabetics did not have a family history of diabetes mellitus.…”
Section: Risk Factors For Family History In Diabetes Mellitussupporting
confidence: 89%
“…These results are in accordance with research by Kistianita, Yunus, & Gayatri (2015) which stated that the majority of patients were in the 55-64 years age group (75%). Research by Isnaini & Ratnasari (2018) also mentioned similar results that the majority of respondents were aged ≥45 years (83%). This is also in accordance with Widyasari's research (2017) which stated that there was a relation between age and diabetes mellitus status and dyslipidemia status.…”
Section: Characteristics Of Diabetics With Complications (Hyperglycemsupporting
confidence: 59%